EXPLORING AL-FĀRĀBĪ’S SECRETS IN HARMONIZING SCIENCE AND RELIGION - Malyuna, Sita Isna; Fuad, Ah. Zakki; Mas’ud, Ali (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
Harmonization between science and religion in al-Fārābī’s thought is an important topic in addressing the challenges of paradigm differences between the two in modern society. This research aims to explore al-Fārābī’s views on the integration of spiritual values and scientific rationality and their relevance to contemporary challenges. Using a qualitative method based on a literature study, this research analyzes al-Fārābī’s works as well as supporting literature that discusses the relationship between science and religion. The results show that al-Fārābī viewed science and religion as two different paths that lead to the same goal, which is the highest human happiness. Science provides rational knowledge to understand the physical world, while religion offers moral guidance to live life. In al-Fārābī’s view, the two complement each other, with science playing a role in revealing the nature of reality and religion providing ethical and spiritual meaning. This research emphasizes that al-Fārābī’s thoughts are relevant in the context of holistic education, ethical development in science and technology, and dialogue between science and religion. This approach can serve as a foundation for moral and rational value-based policies, creating a balance between intellectual progress and social responsibility. Thus, the harmonization of science and religion not only addresses the conflict between the two but also contributes to the construction of a just society with integrity. This research proposes that such integration can be a comprehensive solution to global issues such as technological ethics, climate change, and pluralism.